Synthesis, characterization and biological activities of acridine derivatives and their platinum complexes / Nur Amajeida Ismail - Nur Amajeida , Ismail (2018)
New compounds have been successfully synthesized. The chemical structure of all synthesized compounds, were characterized by using elemental analysis CHN, FTIR, 1H NMR, 13C NMR, APT NMR, Thermal gravimetric analysis (TGA) and single X-ray crystallography. Ligands were derived from acridine and various substituent of aniline, then reacted with Pt(II) salt to form the complexes. The ligand consists of four aromatic rings which three of it are in the form of acridine parent skeleton structure and another one is the substituent of aniline. The synthesized ligands were coordinated to the platinum salt via nitrogen atom, in which the core is in the turn of tetrahedral with either chloride or DMSO attached to it. The acridine acts as a neutral N-monodentate ligand. The reaction of ligands with Pt(II) salt in 1:1 (ligand/metal) molar ratio afforded complexes of Pt G3, Pt G4 and Pt G7. In the presence of sodium acetate, the reaction of acridine with PtCl2DMSO2 remain in base condition to form acridine platinum complexes. The acridine derivatives and its platinum complexes were found to have a significant cytotoxicity value towards three cancer cell lines, namely MCF-7, HL60 and HT29 but not toward the normal liver WRL-68 cell line. The biological activities have been conducted for all of the synthesized compounds, through MTT cytotoxicity assay and selected compound on acute toxicity. All compounds were significantly inhibited the proliferation of MCF-7, HL60 and HT29 cells that was shown in the cytotoxicity assay (IC50 value). Doxorubicin was used as a positive control. Hence the synthesized compounds are promising to be the future drugs as they are highly potent to induce apoptosis in MCF-7 or HL60 cells via intrinsic mitochondrial pathway.